Green Technology: a must or a need in TVET Education in Malaysia? - Kaliappan, Anusuya; Hamid, Hashima (Penerbit UTHM, 2021)
Green Technology is seen as the optimal solution in addressing most of the environmental issues affecting our society today. The movement towards green technology will undoubtedly change the labour market. Although, there were numerous studies been done in regards to green technology but the question remains unanswered when it comes to Vocational Colleges in Malaysia. Therefore, the main goal of this current study is to investigate and develop an in-depth exploration of the need of incorporating Green Technology in one of the most prominent TVET institutions in Malaysia which is the Vocational Colleges. The study uses exploratory sequential mixed method as the research design but only the qualitative approach is being selected to be discussed in this paper. Hence, we report the findings conducted through semi-structured interview by interviewing 7 industrial players in TVET, associated with Vocational Colleges in Malaysia. In relation to the main findings from this study, we found that all 7 participants believe that there is a need to incorporate green technology in the curriculum of Vocational Colleges as to upgrade and fulfill the industry’s needs. Taken together, this finding suggests that educational reform may be the most important tool in the future of green technology in Vocational Colleges and by all means it is defined as a need rather than a must.